Linked data research in adult social care- setting research priorities - Hughes, Tara; Johnson, Eleanor (International Journal of Population Data Science, 2025)
Objectives Social Care Wales have conducted a national research priority-setting exercise as part of the Social Care thematic area within ADR Wales. We would like to present the results and engage in discussions with researchers about how we can develop the research priority areas identified from this exercise into future research activity. Methods Our priority-setting exercise involved individuals from organisations that routinely collect data, people with lived experience of care and support, social care practitioners, third sector partners, researchers and policy makers. We used different methods of engagement, including surveys, focus groups, workshops and interviews to identify a list of research themes for linked data research. We analysed these themes to determine whether they could be explored using linked data research. The final stage of the priority-setting process involved an independently led workshop to develop a consensus for the top 10 research priorities for linked data research within adult social care Results The priority-setting exercise resulted in 10 research priorities for linked data research within adult social care. These priorities also formed the basis of the team's data acquisition activities. As an ambassador within the adult social care sector, Social Care Wales has been promoting the use of linked data research within adult social care. And developing relationships with data owners across Wales, to encourage them to share data within the SAIL Databank. We would like to work with researchers to discuss these research priorities, data availability and collaborations for future research activities. Conclusion Our priority-setting exercise and ongoing data acquisition activities aim to advance linked data research within adult social care and have a strong focus on public involvement and engagement. Our team hope to present their ongoing and planned work at the conference, using this as an opportunity to engage with the research community.